A Comparative Study of the Intellectual Property Rights in Perspective of the Islamic & Western Law - Sana Ullah; Abzahir Khan; Sohail Anwar (Journal of Islamic and Religious Studies, 2018)
Islam always emphasizes to use legal ways and means of earning. In contrary the legal and illegal sources of income have been explained in detail. The “Right of invention” is one of the most discussed issues among the Islamic Jurists. This right is related to the intellectual skills and capabilities of people. However, internationally intellectual property is a known concept that associates with right of publication, right of trademark, patent and right of goodwill et cetera. However, research must be conducted on inquiring rights of intellectual property in Islamic Sharia and comparison of these rights with those in Western laws. In this paper the historical review of the intellectual properly has been presented. Similarly, those various types and concerned ruling have been discussed in contrast with the Islamic and western law on descriptive research methods.